Protumorigenic M2-like phenotype cell infiltration in the melanotic neuroectodermal tumor of infancy This work was presented as poster in XXIII Brazilian Congress of Stomatology and Oral Pathology in July, 2015. - Strieder, Luciana [UNESP]; Carlos, Román; León, Jorge Esquiche; Ribeiro-Silva, Alfredo; Costa, Victor [UNESP]; Kaminagakura, Estela [UNESP] (Elsevier, 2016)
Objective The aim of this study is to report 2 cases of melanotic neuroectodermal tumor of infancy (MNTI), emphasizing the analysis of intratumoral immune cells by immunohistochemistry. Study Design Case 1: A 6-month-old girl presented with a 3-cm tumor in the anterior region of the left maxilla. Case 2: A 4-month-old boy presented with a 4-cm tumor in the anterior region of the left maxilla. Microscopically, case 1 had predominantly neuroblast-like cells supported by fibrillary neuropil-like stroma arranged in an alveolar pattern, whereas case 2 exhibited scattered melanocyte-like and neuroblast-like cells supported by fibrovascular stroma. A large immunohistochemical panel for characterizing intratumoral macrophage and dendritic cell subsets was performed. Results Immunohistochemical analysis indicated positivity for HLA-DR, XIIIa, CD68, and CD163 (range 6%-50%) mainly on the fibrovascular stroma, suggesting M2 macrophage-like cell phenotype. CD138 was overexpressed in the tumor stroma. Conclusions Results suggest the involvement of M2-polarized macrophages in the MNTI pathogenesis, which may act by modulating tumor growth and/or tumor stromal remodeling.